Haitański kryzys bezpieczeństwa a Kenia – dyplomacja wojskowa jako strategia rozwiązania problemu? .......... 125 - Chorąży, Monika; Piotrowicz, Zuzanna (Oblicza dyplomacji, 2025)
THE HAITIAN SECURITY CRISIS AND KENYA: MILITARY DIPLOMACY AS A PROBLEM-SOLVING STRATEGY?The article aims to highlight the crisis in Haiti and draw attention to Kenya’s attempt at military diplomacy, by deciding to send its police forces to the Caribbean country in 2023. This aid, supported by the UN, is intended to suppress the violent activities of gangs that have been destabilizing Haiti’s governmental structures. The motivations behind Kenya’s leadership of the military mission will also be examined, considering the significant geographical distance between the two countries, the lack of their diplomatic relations with each other, and Kenya’s absence from previous peacekeeping missions in Haiti. This aspect has been embedded in the context of the dysfunction of the Haitian state and the country’s long-standing dependence on humanitarian aid.